2010
DOI: 10.1097/smj.0b013e3181bfd2c0
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré Syndrome as a Paraneoplastic Manifestation of Small-Cell Carcinoma of Lung

Abstract: Guillain-Barré syndrome (GBS) encompasses the variants of acute immune-mediated polyneuropathies usually preceded by an infection. A few case reports have associated GBS to neoplastic diseases. It remains unclear whether these are merely coincidental or represent paraneoplastic phenomena. The clinical features of GBS associated with oncological cases do not appear to differ from post-infectious GBS. We report a 74-year-old man in whom small cell carcinoma of lung (SCLC) was diagnosed during a presentation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…Since the present patient had experienced a prior episode of fever, which may have been related to lung carcinoma, such as obstructive pneumonia, the GBS might have been associated with this preceding infection. Several recent case reports have documented an association between GBS and malignancy (4,5). Another previous report (6) described a case of paraneoplastic motor neuropathy in a patient with a high titer of anti-GM1 ganglioside antibodies associated with esophageal cancer.…”
Section: Days After Admissionmentioning
confidence: 99%
“…Since the present patient had experienced a prior episode of fever, which may have been related to lung carcinoma, such as obstructive pneumonia, the GBS might have been associated with this preceding infection. Several recent case reports have documented an association between GBS and malignancy (4,5). Another previous report (6) described a case of paraneoplastic motor neuropathy in a patient with a high titer of anti-GM1 ganglioside antibodies associated with esophageal cancer.…”
Section: Days After Admissionmentioning
confidence: 99%
“…A single case-control study has demonstrated a positive association between GBS and cancer4 and several case reports describe GBS occurring alongside malignancy, including cancers of lung,5 6 bladder,7 blood,8–10 colon11 and skin 12. To our knowledge, we present the first case associated with squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 76%
“…21 In some patients with CIDP, gastrointestinal malignancies were found during follow-up; however, it is unclear whether the CIDP in those cases was a paraneoplastic phenomenon. In populationbased studies, Guillain-Barr2 syndrome has been reported with Hodgkin lymphoma and small cell lung cancer.…”
Section: Case 11-2mentioning
confidence: 99%